PENGARUH DISIPLIN, KOMITMEN ORGANISASI DAN LINGKUNGAN KERJA TERHADAP KINERJA PERSONIL PADA SATUAN SABHARA POLRES KENDARI - Muhlis Muhlis; Nurwati Nurwati; Juharsah Juharsah; Agustinus Tangalayuk; Abdul Razak Yusuf; Hartini Hartini (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2021)
This study aims to examine and analyze the influence of discipline, organizational commitment and work environment on the performance of personnel at the Kendari Police Sabhara Unit. This research is a quantitative approach. The population in this study was the personnel at the Kendari Police Sabhara Unit with a sample of 56 people. The analysis used multiple regression analysis with the help of IBM SPSS 22 Software.  The results showed that (1) Discipline had a positive and significant effect on Personnel Performance at the Kendari Police Sabhara Unit, (2) Organizational Commitment had a positive and significant impact on Personnel Performance at the Sabhara Polres Unit. Kendari, and (3) the work environment has a positive and significant effect on the performance of the personnel in the Kendari Police Sabhara Unit.